Organophosphorus Poisoning - N. E. PORE,; K. N. PUJARI,; S. P. JADKAR, (International Journal of Pharma and Bio Sciences, 2011)
Organophosphate poisoning may cause the life-threatening events resulted in different organs failure. Organophosphorus compounds are extensively used in India as insecticides and most often for suicide purpose. Substantial number of death can be averted by timely treatment and ventilatory support. Organophosphorus (OP) compounds constitute a heterogeneous category of chemicals specifically designed for the control of pests, weeds or plant diseases. Our review article mainly focused on OP poisoning, especially with pesticides, its severity and management of toxic exposure. We conclude that in future, the ministry of agriculture of developing countries, especially India, should concentrate on the optimization and monitoring of usage of OP compounds as pesticides and furthermore, encouraging the farmers to use natural pesticides rather than chemical pesticides .